Financial Literacy and Family Business Sustainability in Jos North Local Government Area, Plateau State - Azi Dabo, Steve; Usman Gwom, Ayuba (Kashere Journal of Politics and International Relations, 2023)
This study examined the influence of financial literacy on family business sustainability in Jos North Local Government Area of Plateau State. Descriptive survey design was used as a guide. A study population 572,700 sourced from the National Population Commission (NPC) Projected Population of Plateau State was considered. A sample size of 400 respondents was selected using stratified and simply random sampling techniques. A structured questionnaire titled ’Financial Literacy and Family Business Sustainability Questionnaire (FILAFB-Q)’ was used for data collection. Face and construct validity of the questionnaire were ascertained by experts, while its reliability was determined using the Cronbach Alpha Coefficient technique where a reliability coefficient of 0.792 was obtained. Face-to-face method of questionnaire administration was used to collect the data. Frequency table, mean, standard deviation and Spearman Rank Order Correlation Coefficient were used for data analysis. The findings revealed that financial literacy skills required include financial planning; financial record keeping and business risk analysis skills, while credit management, portfolio investment and savings decisions are the financial decisions required. The finding revealed that financial literacy has significant positive influence on family business sustainability (p<0.05). It was concluded that financial literacy has significant influence on family business sustainability and the study recommended that family business owners should be trained on financial record keeping, risk analysis, credit management and portfolio investment decision making in order to enhance family business sustainability in Jos North LGA of Plateau State.